Manganese-iron layered double hydroxide: a theranostic nanoplatform with pH-responsive MRI contrast enhancement and drug release. Issue 20 (16th May 2017) - Huang, Guoming; Zhang, Kai-Long; Chen, Shan; Li, Shi-Hua; Wang, Li-Li; Wang, Li-Ping; Liu, Rui; Gao, Jinhao; Yang, Huang-Hao
Abstract : A manganese-iron layered double hydroxide serves as a pH-responsive nanoplatform for simultaneous MRI contrast enhancement and drug delivery. Abstract : Stimuli-responsive theranostic platforms are highly desirable for efficient cancer treatment because of their improved specificity and sensitivity. In this work, we report a manganese-iron layered double hydroxide (MnFe-LDH) for the first time and demonstrate that it can serve as a pH-responsive nanoplatform for cancer theranostics. The MnFe-LDH can respond to the acidic microenvironment of solid tumors to release paramagnetic Mn 2+ and Fe 3+ ions, resulting in great enhancement of the T 1 MRI contrast of the tumor area. In addition, the layered structure enables MnFe-LDH to effectively deliver chemotherapeutic drugs in a pH-controlled manner, and therefore it can simultaneously inhibit the growth of solid tumors. We believe that this novel MnFe-LDH with pH-responsive property holds great promise in cancer theranostic applications.